2017
DOI: 10.1177/003932071704700103
|View full text |Cite
|
Sign up to set email alerts
|

After God but behind the Cross: The Procession as a Way to Re-Encounter God in a Culture beyond Classical Liturgy

Abstract: The authors would like to thank their colleague Joyce Rondaij for her tremendous support and advice on this article. Her knowledge of the theory as discussed in section 3, provided insights that greatly assisted their reflection on the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As empirical research has shown, these are some of the motives people have to actively participate in the procession of the cross (van den Hemel 2020, pp. 70-96; Klomp and Veldsman 2017).…”
Section: Different Approaches To the Eventmentioning
confidence: 99%
“…As empirical research has shown, these are some of the motives people have to actively participate in the procession of the cross (van den Hemel 2020, pp. 70-96; Klomp and Veldsman 2017).…”
Section: Different Approaches To the Eventmentioning
confidence: 99%